2001
DOI: 10.1128/jvi.75.11.5215-5221.2001
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Adenovirus Vector Entry into CD70-Positive B-Cell Lines by Using a Bispecific CD70-Adenovirus Fiber Antibody

Abstract: The consistent presence of the Epstein-Barr virus (EBV) genome in certain malignancies, particularly its nearly universal presence in AIDS-related central nervous system lymphomas (4, 6, 29) and nasopharyngeal carcinomas (31), suggests that EBV itself could serve as a target for the preferential killing of tumor cells using gene delivery methods. Although the use of adenovirus vectors expressing EBV-specific toxins could potentially be useful for treating EBV-positive epithelial cell tumors, EBV-associated B-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Thus, an adenovirus vector is not the optimal vehicle for delivering genes to EBV-positive lymphomas; other vectors would be preferable. Alternatively, approaches which increase adenovirus-mediated gene delivery to lymphocytes, including modification of the viral fiber protein to allow virus binding to alternative cell receptors (9) or the use of bispecific antibodies directed against the adenovirus fiber protein and lymphocyte cell surface antigens (23), may allow the efficient use of the BZLF1 and BRLF1 adenovirus vectors in EBV-positive lymphomas. Westphal et al previously demonstrated that both the BZLF1 and BRLF1 adenovirus vectors induce lytic EBV infection when inoculated directly into an adenovirus-susceptible Burkitt lymphoma tumor (54), thus confirming that if efficient delivery of the BZLF1 or BRLF1 gene can be accomplished in EBV-positive lymphomas, it is likely to induce a similar therapeutic response to that observed for NPC tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an adenovirus vector is not the optimal vehicle for delivering genes to EBV-positive lymphomas; other vectors would be preferable. Alternatively, approaches which increase adenovirus-mediated gene delivery to lymphocytes, including modification of the viral fiber protein to allow virus binding to alternative cell receptors (9) or the use of bispecific antibodies directed against the adenovirus fiber protein and lymphocyte cell surface antigens (23), may allow the efficient use of the BZLF1 and BRLF1 adenovirus vectors in EBV-positive lymphomas. Westphal et al previously demonstrated that both the BZLF1 and BRLF1 adenovirus vectors induce lytic EBV infection when inoculated directly into an adenovirus-susceptible Burkitt lymphoma tumor (54), thus confirming that if efficient delivery of the BZLF1 or BRLF1 gene can be accomplished in EBV-positive lymphomas, it is likely to induce a similar therapeutic response to that observed for NPC tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The approaches by adenovirus-mediated gene delivery to lymphocytes or the use of bispecific antibodies directed against the adenovirus fiber protein and lymphocyte cell surface antigens have been reported in EBV-positive lymphomas. 106 Other possibilities are also being investigated.…”
Section: Zta As a Target Of Anticancer Therapymentioning
confidence: 99%
“…Advantages of the two-component system are that many receptors can be targeted and there is no need to genetically engineer the vector. A commonly used example of the two-component method employs bispecific antibodies, 31 one to the fiber and the other to a cell receptor expressed for example on tumor cells 32 or cell surface antigen that is upregulated in angiogenic areas of tumors. 33 This approach has been used frequently to demonstrate proof of concept of a given targeting ligand.…”
Section: Targeting Of Ad Vectors Will Improve the Therapeutic Indexmentioning
confidence: 99%